2011 International Conference on Electrical and Control Engineering 2011
DOI: 10.1109/iceceng.2011.6057602
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of earth surface potential distribution of HVDC due to finite element and multi-layer soil

Abstract: Strong electric field will be produced in the earth around the grounding poles when HVDC transmission system operates in ground-return mode, which would have effects on the electric power equipments and the underground metal pipes nearby. This paper builds a model of multi-layer soil and a typical soil model on the basis of actual distribution of soil around the grounding poles, and then performs a calculation of earth surface potential distribution of typical soil model by finite element method. A comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…So, the ring electrode has more stable ESP, better current density distribution and resistance-to-ground. It is found that the calculation results in this paper can accurately reflect the current dispersion characteristics of grounding electrodes by comparing with the conclusions in [27,28].…”
Section: Three Common Kinds Of Grounding Electrodessupporting
confidence: 60%
“…So, the ring electrode has more stable ESP, better current density distribution and resistance-to-ground. It is found that the calculation results in this paper can accurately reflect the current dispersion characteristics of grounding electrodes by comparing with the conclusions in [27,28].…”
Section: Three Common Kinds Of Grounding Electrodessupporting
confidence: 60%